2013
DOI: 10.1002/ppsc.201300111
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Response of Human Oral Epithelial Cells to Internalized Silica Nanoparticles

Abstract: Silica nanoparticles (SiO2 NPs) are one of the most widely used engineered nanoparticles and can been found in a wide range of consumer products. Despite their massive global production scale, little is known about their potential effects in the context of unintended exposure or ingestion. Using TR146 cells as an in vitro model of the human oral buccal mucosa, the uptake, spatial intracellular distribution, reactive oxygen species (ROS) production, inflammatory response, and cytotoxic effects of commercial SiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 66 publications
3
19
1
Order By: Relevance
“…Thus, we investigated the induction of intracellular reactive oxygen species (ROS) by ZnO NP. Previous study had reported that ZnO NP are able to disturb the intracellular oxidative stress balance and consequently triggered other detrimental events in the cell . Similarly, we observed an elevation of intracellular ROS in the endothelial cells after 3 h of ZnO NP treatment (Figure D) but not at the early timepoint.…”
Section: Resultssupporting
confidence: 78%
“…Thus, we investigated the induction of intracellular reactive oxygen species (ROS) by ZnO NP. Previous study had reported that ZnO NP are able to disturb the intracellular oxidative stress balance and consequently triggered other detrimental events in the cell . Similarly, we observed an elevation of intracellular ROS in the endothelial cells after 3 h of ZnO NP treatment (Figure D) but not at the early timepoint.…”
Section: Resultssupporting
confidence: 78%
“…These ZnO NM‐induced IL‐1β and IL‐18 overexpressions suggested that downstream activation of nuclear factor kappa‐B (NF‐κB) might have occurred, as NF‐κB is the master transcription factor in driving inflammatory responses. Previous studies also confirmed that NMs such as SiO 2 , TiO 2 , and hydroxyapatite were capable of activating NF‐κB signaling events . To complement our analysis at the transcriptional level, immunostaining was employed to examine the spatiotemporal expression of NF‐κB proteins in the 3D SW480 culture.…”
Section: Resultsmentioning
confidence: 61%
“…Previous studies have demonstrated that SiO 2 nanoparticles may be trapped within the endosomes, lysosomes, or even interact with membrane-bound organelles such as the mitochondria and cell nucleus. [26] In our experiment, the cells were exposed to DOX-loaded PAA-modified UCNPs with different concentrations before and after NIR irradiation. As shown in Figure 6d, remarkably low contents of DOX drug (in red color) could be observed in the cells without NIR light irradiation (808 nm), even at a high particle concentration (0.1 µg mL −1 ).…”
Section: Resultsmentioning
confidence: 99%